Development of efficient methods for prediction of BLEVE pressure in open space and loading on structures - Wang, Yang (Curtin University, 2024)
This thesis offers valuable insights into BLEVE pressure prediction and its implications on structural response predictions and BLEVE resistant design. The empirical formulae and charts for predicting BLEVE pressure-time profile, including BLEVE pressure wave in open space and BLEVE loads acting on a structure, are derived, which can provide engineers with practical tools for addressing BLEVE- resistant structural design and optimizing safety measures.